Influence of COVID-19 pandemic on stress levels of urologic patients - Del Zingaro Michele (De Gruyter, 2021)
Several studies have shown the consequences of COVID-19 pandemic on perceived stress of different populations, but none of them analyzed urological patients who underwent elective surgery.